SISTEM AKUNTANSI PENGELOLAAN DANA DESA DI DESA KANAUNGAN KECAMATAN LABAKKANG KABUPATEN PANGKAJENE DAN KEPULAUAN - Arida Supiati; Chairul Burhanuddin; Ainun Arizah (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Abstract : This study aims to understand and analyze the accounting system for managing village funds in Kanaungan Village, Labakkang Sub-district, Pangkajene and Islands Regency. The research uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results show that the accounting system implemented in Kanaungan Village follows existing regulations, such as Minister of Home Affairs Regulation No. 113 of 2014, and utilizes the Village Financial System (Siskeudes) application. The village fund management process includes planning, implementation, administration, reporting, and accountability stages. However, challenges remain, such as limited human resource capacity and lack of technical accounting knowledge. Continuous training and strict supervision are required to enhance the transparency and accountability of village financialÂ management.Â Keywords: Accounting System, Village Found, Siskeudes, Financial Management